Fluid damper that applies electric and magnetic fields to a conductive fluid and ferrite particles - Taichi MATSUOKA; Tomohiro SUGITA (Nihon Kikai Gakkai ronbunshu, 2014)
A fluid damper that applies electric and magnetic fields to a conductive fluid and ferrite particles is developed in order to act as both of a passive and a semiactive type vibration control device. The damper consists of a long by-pass pipe, electromagnets, electrodes, a piston, a cylinder, a conductive fluid, and ferrite particles. The eight electromagnets are installed around the by-pass pipe. The eight electrodes are fixed, and the ferrite particles are put inside the by-pass pipe, respectively. The conductive fluid is entirely filled in the cylinder, the tube and the by-pass pipe. Magnetic flux density in the by-pass pipe can be switched by not only applied voltage of the coil but also multi pole conditions of the electromagnets. An electromagnetic induction force of the conductive fluid and particles is caused by Fleming's left hand rule when both of magnetic and electric fields are applied in transverse. Furthermore, the ferrite particles virtually act as an artificial orifice due to clustering, therefore the resisting force can be changed. Test damper is manufactured. Theories of damping, magnetic induction and liquid inertia effects are introduced, respectively. Magnetic flux densities in four cases of multi pole conditions are measured, and analyzed by FEM. Resisting force characteristics of the test damper using the conductive fluid with the ferrite particles are measured under sinusoidal harmonic excitation. The experimental results are compared with the theoretical results. Finally, the effects of electromagnetic induction and a feasible study are confirmed experimentally and theoretically.